Doula Care Supports Near‐Universal Breastfeeding Initiation among Diverse, Low‐Income Women. (9th July 2013) - Kozhimannil, Katy B.; Attanasio, Laura B.; Hardeman, Rachel R.; O'Brien, Michelle
Abstract : Introduction: Breastfeeding initiation rates in the United States have risen in recent years. However, there are notable disparities by socioeconomic status and race/ethnicity. Previous research has suggested that care from a doula (a trained professional who provides nonmedical support during the perinatal period) may increase breastfeeding initiation. The goal of this analysis was to study whether doula support may be associated with breastfeeding initiation among low‐income, diverse women. Methods: We compared breastfeeding initiation rates (means and 95% confidence intervals) for 1069 women who received doula care from Everyday Miracles, a Minnesota‐based organization that employs a diverse group of certified doulas, to a state‐based sample of women with Medicaid coverage who gave birth in 2009 or 2010 and participated in the Minnesota Pregnancy Risk Assessment Monitoring System survey (weighted n = 51, 721). Results: Women who had doula‐supported births had near‐universal breastfeeding initiation (97.9%), compared with 80.8% of the general Medicaid population. Among African American women, 92.7% of those with doula support initiated breastfeeding, compared with 70.3% of the general Medicaid population. Discussion: These results suggest that access to culturally appropriate doula care may facilitate higher rates of breastfeeding initiation. When supported in their nonmedical needs by birth doulas, the diverse, low‐income patients of midwives and other maternity care providers may have a greater likelihood of initiating breastfeeding and experiencing the maternal and infant health benefits associated with breastfeeding.